Analysis of determinants of dividend policy in UK - Leung, Yiu Man (2006)
This dissertation aims to study the determinants of dividends policy in UK since most empirical evidence is focused on US companies, the results from US firms may not be fully reflected the condition of UK companies. Another objective is to investigate the consistence of the dividend policy determinants.